Personalization of Genome-Based Anesthesia for Cardiovascular Patients: Pharmaceutical Strategies for Dose Optimization and Risk Mitigation in High-Risk Surgeries - Andrés Felipe Rodríguez Galeano; Angel Mamani-Ruelas; Jose Edgar Vilca Vera; Joseph Alejandro Veraza Almeida (International Journal of Medical Toxicology and Legal Medicine, 2024)
Personalized anesthesia, especially for cardiovascular patients, emerges as a promising strategy to minimize risks and optimize doses in high-risk surgeries. Genetic variability between individuals affects the response to anesthetic agents, which implies the need to adapt doses according to the patient’s genetic profile. This study reviews recent scientific evidence on pharmacogenomics applied to cardiovascular anaesthesia, identifying key genes and biomarkers that allow for the adjustment of anaesthetic strategies. Through an experimental design, the efficacy of a personalized methodology compared to standard approaches was evaluated, highlighting the reduction of perioperative complications and improving outcomes in postoperative management.